Pre-Operative Predictors for Post-Operative Pneumonia in Aneurysmal Subarachnoid Hemorrhage After Surgical Clipping and Endovascular Coiling: A Single-Center Retrospective Study - Yuan, Kexin; Li, Runting; Zhao, Yahui; Wang, Ke; Lin, Fa; Lu, Junlin; Chen, Yu; Ma, Li; Han, Heze; Yan, Debin; Li, Ruinan; Yang, Jun; et al. (Frontiers in Neurology, 2022)
Objective: Postoperative pneumonia (POP) is one of the major complications after aneurysmal subarachnoid hemorrhage (aSAH) associated with postoperative mortality, prolonged hospitalization, and increased medical cost. Early recognition of pneumonia and more aggressive management may improve patient outcomes. Methods: We retrospectively reviewed aSAH patients between January 2015 and December 2020. Baseline clinical characteristics, imaging data, and inflammatory biomarkers were reviewed. The risk factors derived from multivariate logistic regression of surgical clipping and endovascular coiling were analyzed. The AUC was used to calculate each independent predictor’s prediction ability. Results: A total of 843 patients were enrolled. Compared with patients in the EC group, the incidence of POP was higher in the SC group (143/414 [34.54%] vs 114/429 [26.57%], p = 0.015). In the EC group, multivariate analysis revealed that age (p = 0.001; OR = 1.04, 95% CI = 1.02 – 1.07), posterior circulation aneurysms (p = 0.021; OR=2.07, 95% CI=1.14 – 3.83), higher neutrophil (p < 0.001; OR = 1.13, 95% CI = 1.06 – 1.21), World Federation of Neurosurgical Societies (WFNS) grade 4 or 5 (p < 0.001; OR = 4.84, 95% CI = 2.67 – 8.79), modified Fisher Scale (mFS) grade 3 or 4 (p = 0.022; OR = 2.60, 95% CI = 1.15 – 5.89), acute hydrocephalus (p = 0.048; OR = 1.74, 95% CI = 1.01 – 3.00) were independent risk factors for POP. In the SC group, multivariate analysis revealed that age (p = 0.015; OR = 1.03, 95% CI = 1.01 – 1.05), WFNS grade 4 or 5 (p = 0.037; OR = 1.76, 95% CI = 1.03 – 3.00), heart disease (p < 0.001; OR = 5.02, 95% CI = 2.03 – 12.45), higher white blood cell (p < 0.001; OR = 1.13, 95% CI = 1.07 – 1.20) and mFS grade 3 or 4 (p = 0.019; OR = 2.34, 95% CI = 1.15 – 4.77) were independent risk factors for POP. Conclusions: Patients treated with SC are more likely to develop POP. Comprehensive preoperative evaluation of patients may help physicians better predict POP and implement preventive measures to improve outcomes.